The Impact Of Teachers’ Differentiated Initiations And Feedback On Students’ Responses: A Model Based On Audience Design And Bloom’s Taxonomy Of Cognitive Domains - ZAGHAB, MAI IDREES (2023)
The main objective of this study was to gain insights into students' verbal responses and, consequently, offer valuable information and recommendations to teachers and curriculum designers on ways to cater to individual students' learning needs and enhance the quality of students' responses. This study aimed to investigate the impact of incorporating the audience design model, Bloom's taxonomy, and the differentiated instruction approach on students' verbal responses.Data for this research was gathered from 5 observed classes and through semi-structured interviews with 12 high school teachers and 5 high school students. The research sought to address the following research questions: To what extent does integrating the audience design model in teachers’ differentiated initiations and feedback improve students’ verbal responses? To what extent does employing Bloom’s Taxonomy of Cognitive Domains when tailoring teachers’ initiations and feedback help improve students’ verbal responses? The study, conducted in a private school in Dubai, employed qualitative research methods to analyse and synthesise data into several themes related to differentiated instruction, classroom interactions, teacher talk time vs. student talk time, and audience design. These themes provided a comprehensive understanding of the data. The findings indicated that teachers' differentiated instruction and feedback, especially when considering the audience design model, significantly impacted both the quantity and quality of students' verbal responses. However, the study had faced some limitations, as a result, several recommendations were put forward to assist educators and curriculum designers in facilitating the implementation of differentiated instruction and feedback. These recommendations included promoting research, collaboration, and presentation skills. Furthermore, it highlighted the significant role of curriculum publishing companies in offering ready-made questions and activities to ease the burden on teachers in terms of time and effort.